Geochemical processes controlling silica concentrations in groundwaters of the Salado River drainage basin, Argentina - Miretzky, Patricia (2001)
Chemical analyses of dissolved silica in the shallow groundwater of the lower part of the Salado River drainage basin indicate that silica values averaged 60 ppm. The groundwaters are oversaturated in relation to quartz, Na-plagioclase, K-feldspar, and the weathering of quartz and aluminosilicates appear to have little control on silica concentrations in solution. Groundwater is undersaturated with respect to amorphous silica present in the loessic sediments, and these sediments are specially important in the control of the groundwater composition. The sources of amorphous silica are volcanic glass shards and biogenic silica derived from plant (silicophytoliths, diatom frustules) or animal remains (sponge spicules) also present in the Pampean loess. Silicophytoliths and diatoms have also been reported in A soil horizon samples. The dissolution of amorphous silica most likely controls the high dissolved silica concentrations in groundwater.